2015
DOI: 10.1039/c5nr04783h
|View full text |Cite
|
Sign up to set email alerts
|

Black-CuO: surface-enhanced Raman scattering and infrared properties

Abstract: Large surface area samples of nanotextured black CuO were prepared by chemical etching of Cu for use in surface-enhanced Raman scattering (SERS). The SERS intensity of a self-assembled monolayer (SAM) of thiophenol was proportional to the thickness of a nanoscale-conformal Au film deposited by magnetron sputtering over the black CuO. A very high SERS yield of ∼10(4) counts per s per mW was observed for the thiophenol SAM on the thickest Au films studied here. Synchrotron X-ray photoelectron spectroscopy was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…1(d)). Noteworthy, the density of the spikes is similar to those for b-Si, while the SERS yield is also comparable, as shown in previous studies [32,34,35]. Meanwhile, the density of the surface textures both substrate ensure that several (≈10-20) randomly arranged spiky nano-features will be always within the laser irradiated spot (see Methods for details).…”
Section: Resultssupporting
confidence: 80%
“…1(d)). Noteworthy, the density of the spikes is similar to those for b-Si, while the SERS yield is also comparable, as shown in previous studies [32,34,35]. Meanwhile, the density of the surface textures both substrate ensure that several (≈10-20) randomly arranged spiky nano-features will be always within the laser irradiated spot (see Methods for details).…”
Section: Resultssupporting
confidence: 80%
“…Mechanisms controlling crystallisation of protein coils via ordered hydrogen bonding and their unzip-decomposition at different annealing temperatures, laser and electron beam exposure conditions are of interest for applications in material science and bio-medical fields [11,12,13]. Silk can be used as a bio-compatible scaffold [14] with water solubility dependent on its crystallinity [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident from the comparison of Figures 4 and 5 that the intensity of spectra in the case of the Pd coated black-CuO electrode was about 10 times less. This, most likely, should be attributed to blocking of the black-CuO surface by Pd, rather than a decrease in electrode surface area, because the evaporated ∼200 nm thick Pd layer could not significantly reduce the true surface area of the electrode, as we found in earlier SERS studies [21]. The same electrode was used in both experiments.…”
Section: Spectroelectrochemical Measurementsmentioning
confidence: 81%
“…A flat circular copper electrode of ca. 5 mm in diameter, press-fitted into a Teflon rod, was oxidized chemically as described in our previous paper [21] to produce a SERS active nanostructured Cu(II) oxide layer, further in the text referred to as black-CuO because of its black appearance due to its anti-reflective surface texture. Using synchrotron X-ray surface analysis, we confirmed that only CuO was present on the surface of black-CuO [21] prepared by the method used in this study.…”
Section: Samples For Spectroelectrochemical Measurementsmentioning
confidence: 99%